Improving Children's Science Skills Through Play Activities in Outdoor Play - Hasmawaty Hasmawaty; Usman Usman; Intisari Intisari (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
The natural environment provides a variety of stimuli to develop skills for direct observation and simple research for early childhood. They are invited to observe, identify patterns, collect data, and make conclusions based on evidence obtained through scientific procedures. These skills are essential in the scientific method and strengthen a child's scientific abilities. This study aimed to determine the skills of children's science processes when playing outdoors. This experimental research with a type of quasi-experimental design, using samples of students in group B of Taman Paud Doa Ibu Kindergarten, totaling 20 students. The results showed that outdoor play activities improved students' scientific abilities with indicators of children's ability to observe, compare, and classify. The results of this study also show that children's enthusiasm for learning and give birth to children's feelings of curiosity are very high.